2015
DOI: 10.1088/0963-0252/24/5/055005
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of an underwater steam plasma discharge as alternative to air plasmas for water purification

Abstract: An underwater steam plasma discharge, in which water itself is the ionizing media, is investigated as a means to introduce advanced oxidation species into contaminated water for the purpose of water purification. The steam discharge avoids the acidification observed with air discharges and also avoids the need for a feed gas, simplifying the system. Steam discharge operation did not result in a pH changes in the processing of water or simulated wastewater, with the actual pH remaining roughly constant during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…In‐liquid plasma technologies can be categorized into two types, based on the electrode configuration. In the first type, both electrodes are submerged in the liquid . Submerged electrode type discharge requires bubble generation for plasma ignition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In‐liquid plasma technologies can be categorized into two types, based on the electrode configuration. In the first type, both electrodes are submerged in the liquid . Submerged electrode type discharge requires bubble generation for plasma ignition.…”
Section: Introductionmentioning
confidence: 99%
“…Submerged electrode type discharge requires bubble generation for plasma ignition. The bubbles are generally generated by joule heating or ultrasonication . Kang et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decades, dielectric barrier discharges (DBDs) have attracted growing attention in organic pollutants removal from water [1][2][3][4][5]. It is demonstrated that electrical discharges of DBD applied in water could directly or indirectly cause organic compound degradation by © 2016.…”
Section: Introductionmentioning
confidence: 99%